The Modification of Mythological Archetypes “son” and “father” in Joyce's Novel “Ulysses” - N. A. Karlik (Дискурс, 2024)
Introduction. This article delves into the analysis of modifications of mythological and   Christian archetypes in Joyce's work, particularly focusing on the novel “Ulysses” and   examining characters playing familial roles of “son” and “father”. The interest in family ties   is explored considering the atmosphere of creating the novel and biographical aspects.   Family roles are viewed through the modifications of a significant biblical narrative for the   author – the story of the prodigal son. The goal of the analysis was to showcase which vector   the author chose and why to develop this archetypal theme in “Ulysses”. The main role,   adapted to the familial setting through a new interpretation of the parable, was identified   and analyzed as the role of the “prodigal father”.   Methodology and sources. The textual analysis in the article was conducted in the   traditions of post-structuralism: additional intertexts were used to augment the familial   relationships of the novel's characters with new meanings.  Results and discussion. Through the modernization of familial archetypes in the novel, this   article demonstrates how Joyce, as a representative of world literature, treated these   templates. His myth-making involved selectively drawing from source materials that suited   his specific purposes, whether it was the story of Odysseus or the parable of the prodigal   son. He approached the archetypal text liberally, using it as a systematizing mechanism to   elevate contemporary issues to a more universal level.   Conclusion. The article sequentially examines canonical archetypal roles and various   possible readings of the source text, influenced by the author's personal experiences   (biographical) as well as the cultural-historical context, shifting peripheral components of   the parable to dominant positions.